Evaluation of the Utility of the Revised Get Ready to Read! for Spanish-Speaking English-Language Learners Through Differential Item Functioning Analysis. (September 2015) - Farrington, Amber L.; Lonigan, Christopher J.; Phillips, Beth M.; Farver, JoAnn M.; McDowell, Kimberly D.
Children who are Spanish-speaking English-language learners (ELLs) comprise a rapidly growing percentage of the population in U.S. schools. To determine which of these children have weaker emergent literacy skills and are in need of intervention, it is necessary to assess emergent literacy skills accurately and reliably. In this study, 1, 318 preschool children were administered the Revised Get Ready to Read! (GRTR-R), and item-response theory analyses were used to evaluate and compare the item-level characteristics of the measure. Results of differential item functioning (DIF) analysis identified significant DIF for seven items. Correlational analysis demonstrated that ELL children's scores on the GRTR-R were more strongly related to oral language skills than were non-ELL children's scores. These results support the use of the GRTR-R as a screening tool for identifying ELL children who are at risk for developing reading problems.